Omani Frankincense nanoemulsion formulation efficacy and its latent effects on biological aspects of the spiny bollworm Earias insulana (Boisd.) - Metayi, Mervat H.; Abd El-Naby, Shimaa S.; El-Habal, Noha A.; Fahmy, Heba H.; Abdou, Mona S.; Ali, Baber; Abdel-Rheim, Khaled H.; Abdel-Megeed, Ahmed (Frontiers in Physiology, 2022)
Our research shed light on the perspective of formulation technology regarding its responsibility to provide phyto-insecticides that are worthy of research into potential novel applications. There has been an increase in interest in using nanoemulsion as a new formulation in a variety of sectors during the last several decades. Aqueous dispersions of Omani frankincense nanoemulsion were successfully prepared by a high-pressure homogenization method using a high-energy ultra-sonication process and Tween 80 as the surfactant. The properties of the frankincense nanoemulsion, such as particle size and polydispersity index (PDI), were investigated. The morphology of frankincense nanoemulsion was observed by transmission electron microscopy (TEM). Gas chromatography/mass spectrometry (GC/MS) was used to identify the chemical profiles of frankincense essential oil. Furthermore, insecticidal effects against 2nd instar larvae of the spiny bollworm, E. insulana, as well as their latent effects on the different stages of the survived larvae were studied. The results revealed that a successful frankincense nanoemulsion with a mean size of 41.30 nm and a homogeneous globule size distribution with a PDI of 0.26, and the morphology of the frankincense nanoemulsion were visualized in a spherical shape. The main constituents identified in frankincense oil were α-pinene (15.52%); monolinolenin (12.92%); and geranylgeranyl acetate (9.99%). The results showed significant insecticidal activity against larval and pupal stages and considerably decreased the pupation percentage. On the other hand, the latent effects of the frankincense nanoemulsion on E. insulana resulted in a complicated symptom that showed a higher prolongation of larval and pupal durations and considerably lower treated larvae and pupal weight. Additionally, frankincense nanoemulsion dramatically influenced the adult emergence percentage. It also caused a significantly lower hatchability percentage compared to the untreated control. The concentrations used and the types of mating-combination have a significant effect on the fecundity of E. insulana. This novel frankincense nanoemulsion formulation could be used in strategies to control the Spiny Bollworm on cotton plants.